The Self-Stigma of Suicide Attempt Survivors. Issue 1 (2nd January 2020) - Sheehan, Lindsay; Oexle, Nathalie; Dubke, Rachel; Wan, Hoi Ting; Corrigan, Patrick W.
Abstract : Although suicide attempt survivors report feelings of shame and stigmatization, no published scale measures self-stigma experienced by attempt survivors. This article describes the creation and validation the Self-Stigma of Suicide Attempt Scale (SSSAS). In this study, the SSSAS was validated in an online sample ( n  = 292) of suicide attempt survivors. Results supported the progressive model of self-stigma, wherein a substantial proportion of suicide attempt survivors were aware of stigma, but fewer applied that stigma to themselves or felt harmed by it. Reliabilities of SSSAS subscales were high. Harm subscale scores were correlated with depression, self-esteem, recovery, empowerment, and stigma stress in the expected directions. Future research can seek to further validate the scale and explore relationship between self-stigma and other constructs.